Site-specific pharmaco-laser therapy: A novel treatment modality for refractory port wine stains - van Raath, M. Ingmar (J Clin Transl Res, 2019)
Despite extensive efforts to optimize laser therapy, i.e., the current gold standard treatment, a majority of port wine stain (PWS) patients responds suboptimally to laser therapy. This paper describes the niceties of a novel PWS treatment modality termed site-specific pharmaco-laser therapy (SSPLT). In contrast to the classic approach of enhancing the extent of intravascular photocoagulation (the photothermal response), SSPLT focuses on optimization of post-irradiation thrombus formation (i.e., the hemodynamic response) by combining conventional laser therapy with the administration of thermosensitive drug delivery systems that encapsulate prothrombotic and antifibrinolytic drugs. The aim of SSPLT is to instill complete lumenal occlusion in target vessels, which has been linked to optimal PWS blanching. RELEVANCE FOR PATIENTS: The current treatment options for PWS patients are limited in efficacy. Novel therapeutic modalities are needed to more effectively treat patients with recalcitrant PWSs. SSPLT is an experimental-stage treatment modality that could serve as an adjuvant to pulsed dye laser therapy for a selected group of patients whose PWS is ill-responsive to standard treatment. The expected clinical result of SSPLT is improved lesional blanching.